A glimpse at Bangladeshi fashion and lifestyle industry through ICE Today Magazine - Sulaiman, Khandokar Asif (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2017.